DECISION SUPPORT SYSTEM SELECTION OF THE BEST ANDROID SMARTPHONE USING THE METHOD OF MOORA - Ernawati, Siti; Al Hakim, Imam Taftazani; Tuslaela, Tuslaela (LPPM Universitas Nusa Mandiri, 2020)
In the current conditions of each person must have a smartphone due to a lot of activities are done online. These activities can be in the form of learning, purchasing, transportation, and so forth. Smartphones offered currently have various specifications, sometimes prospective buyers feel confused to choose a smartphone as what they need. To overcome the problems in the decision of the selection of the best android smartphone that is with the decision support system using the method of Multi-Objective Optimization based on Ratio Analysis (MOORA). In this study, the data collected based on the 100 questionnaires that were distributed. The criteria used, namely random access memory (RAM), camera, price, storage capacity, battery life, and screen size. The results of the calculation obtained in this study determine each brand and type of smartphone the best android. Expected in this study can help prospective buyers who are confused in choosing the best android smartphone